Cadinapyridine sesquiterpene alkaloids from Artemisia annua and in vitro cytotoxicity and antiplasmodial activities - Nicolas Fabre; Adrien Vitrai; Sandra Bourgeade-Delmas; Nathalie Saffon-Merceron; Abdou Madjid Olatoundé Amoussa; Latifou Lagnika; Agnès Aubouy; Valérie Jullian (PLoS ONE, 2025)
Artemisia annua L. (A. annua) is a medicinal herb that has been used for the last two millennia to treat various diseases. In African countries, teas prepared from cultivated A. annua have been used to treat malaria for the past three decades. In another work, our team investigated the antiplasmodial efficacy of these traditional preparations using a Liquid-Chromatography-Mass Spectrometry metabolomic approach on various teas prepared from different batches of A. annua collected in Benin and in France and highlighted an original nitrogenous compound. The present work aimed to isolate and characterize its structure. Therefore we describe the fractionation of an alkaloid extract from a Beninese sample of the plant’s aerial parts led to the isolation of two previously undescribed alkaloids, annuanine A (1) and annuanine B (2) along with the known fabianine (3), all possessing a very unusual skeleton. Their structures were determined through NMR and MS data analyses. The structure of 1 was further confirmed by single-crystal X-ray structural analysis. Compounds 1 and 2 were evaluated for cell-growth inhibition on Caco-2, VERO, and Thp1 cells, as well as on the Plasmodium falciparum FcB1 strain. Unfortunately, the two compounds 1 and 2 were inactive in these in vitro models. Comparison of LC-HRMS data between annuanine B and A. annua tea allowed us to identify it as the nitrogenous compound highlighted by our previous study. These results enhance the chemical knowledge of this well-known ethnopharmacological herb and highlight a very rare alkaloid skeleton that may have formed from the degradation of artemisinin during plant storage.